Factors associated with anxiety in pre-lower gastrointestinal endoscopy in inflammatory bowel disease patients: a systematic literature review. (1st October 2020) - Al-Dibouni, Ziyad; Poullis, Andrew
Abstract: Background: Inflammatory bowel disease (IBD) affects more than 300 000 people in the UK alone. These patients will frequently require gastrointestinal (GI) endoscopic assessment and surveillance of their disease, which can cause pre-procedure anxiety. A better understanding of procedure-related anxiety can help develop measures to reduce it and improve patient experience. Aims: A systematic literature review was conducted to identify the factors that are associated with pre-lower gastrointestinal endoscopy anxiety in inflammatory bowel disease (IBD) patients. Methods: Electronic databases were searched for studies that evaluated anxiety with GI endoscopic procedures in IBD patients. Studies were independently reviewed by an author, extracting data and assessing quality. The main outcomes were the prevalence of pre-procedure anxiety, patient concerns, tolerance and interventions in IBD patients. Results: In total, 77 studies were identified for inclusion. No studies specifically explored the prevalence and severity of anxiety in IBD patients. The studies that investigated pre-procedure anxiety identified that high levels were seen pre-procedure, with areas of anxiety-related concerns including bowel preparation, potential discomfort and the stigma of embarrassment. Conclusions: Many patients undergoing GI endoscopic procedures experience anxiety. Improving the ways in which pre-procedure information is delivered can help in reducing this anxiety. However, the prevalence and severity of and best method of intervention for this anxiety in IBD patients are unclear, providing areas for further research.